Developing a Phase and Intensity Measurement Technique with Multiple Incident Angles under Surface Plasmon Resonance Condition - Han, Chien-Yuan; You, Du Cheng; Chen, Yi-Ren; Chao, Yu-Faye (My University, 2013)
This work presents the application of a focused beam polarizer-sample-analyzer imaging ellipsometer in measuring the ellipsometric parameters under the surface plasmon resonance condition. By using a cylindrical lens to produce fan shaped beam with multiple incident angles, three-intensity measurement technique can measure the ellipsometric parameters against each incidence but without the need of calibrating the azimuth errors of polarizer and analyzer. As a result of multiple incident angles approach, the whole SPR curve can be obtained without rotating the sensor chip. The intensity and phase response in the air and water interface of the sensor chip were demonstrated, and almost all measured results are close to the theoretical model.
Keywords: focused beam; ellipsometry; surface plasmon resonance